Behavioural Pharmacology Of Mitragyna speciosa Korth Standardized Methanol Extract In An Animal Model - Senik @ Nawi, Mohd Harizal (2011)
Mitragyna speciosa Korth is one of the species of plant used by locals especially in Thailand and Malaysia in treating diarrhea, worm infestations and acts as an analgesic and antipyretic. There is scarcity of information in the literature regarding to toxicity, pharmacology and behaviour effect of this indigenous medicinal herb on. Therefore, this study was conducted to determine the acute toxicity level of Mitragyna speciosa Korth methanol extract (MS) in vivo, to evaluate cognitive functions of rats after acute exposure of MS using avoidance tasks and to delineate the effect of MS in inducing neuronal potentiation of rats’ hippocampus cells using extracellular recording.